SUFI MUSIC AS A MEDIUM OF SPIRITUAL AND CULTURAL CONTINUITY IN THE MODERN WORLD - Ergashov Abbos Baxridinovich (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2026)
This article explores Sufi music as a significant medium for maintaining spiritual depth and cultural continuity in the modern world. It analyzes how Sufi musical traditions, rooted in mystical philosophy, continue to influence contemporary cultural practices, artistic creativity, and spiritual experience. The study emphasizes the transformative power of Sufi music in addressing modern existential challenges, promoting ethical values, and sustaining intercultural dialogue. By examining its spiritual symbolism, aesthetic qualities, and social functions, the article highlights the enduring relevance of Sufi music in contemporary global culture.